A review of security attacks on IEC61850 substation automation system network - Rashid M.T.A.; Yussof S.; Yusoff Y.; Ismail R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; Computer crime; Computer system firewalls; Electric substations; Intrusion detection; Local area networks; Mobile security; Security of data; Wide area networks; GOOSE; IEC 61850; Intrusion Detection Systems; Security attacks; Security vulnerabilities; SMV; Substation Automation Systems; Substation networks; Network security